Immunological properties of Hypnale hypnale (hump-nosed pit viper) venom: Antibody production with diagnostic and therapeutic potentials - Tan, Choo Hock; Tan, Nget Hong; Sim, Si Mui; Fung, Shin Yee; Gnanathasan, Christeine Ariaranee (Elsevier, 2012)
Envenomation by hump-nosed pit viper (Hypnale hypnale, Hh) in Sri Lanka has caused significant morbidity and mortality, attributed to 35 of total venomous snakebites. In Southwestern India (Kerala), H. hypnale was increasingly identified as a dangerous and common source of envenomation, second to the Russell's viper but ahead of the cobra bites. Unfortunately, there is still no specific antivenom to date. This study aims to investigate the immunological properties of the venom and to assess the feasibility of specific Hh antivenom production as well as the development of a diagnostic assay. Hh venom elicited satisfactory titers of anti-Hh IgG in rabbits after 3rd immunization. The anti-Hh IgG, isolated with caprylic acid precipitation method, was effective in neutralizing the venom lethality (potency = 48 LD50 per ml IgG) as well as its procoagulant, hemorrhagic and necrotic effects, indicating the possibility to produce the specific antivenom using the common immunization regime. Cross-reactivity studies using indirect ELISA showed that anti-Hh IgG cross-reacted extensively with several Asiatic crotalid venoms, particularly that of Calloselasma rhodostoma (73.6), presumably due to the presence of venom antigens common to both snakes. Levels of immunological cross-reactivity were vastly reduced with double-sandwich ELISA. Further work demonstrated that the assay was able to distinguish and quantify venoms of H. hypnale, Daboia russelii and Echis carinatus sinhaleyus (three common local viperid) used to spike human sera at various concentrations. The assay hence may be a useful investigating tool for diagnosing biting species and studying the time course profile of venom concentrations in blood.